Expectations, challenges, and opportunities : beyond being a south american woman at the Society of Biblical Literature - Flammini, Roxana (2019)
Fil: Flammini, Roxana. Pontificia Universidad Católica Argentina. Facultad de Ciencias Sociales. Instituto de Investigaciones; Argentina